Pengaruh Pemberian Video Dukasi Sadari Terhadap Tingkat Pengetahuan Siswi Dalam Melakukan Praktik Sadari - Intan Wahyu Anggraini; Esitra Herfanda; Elika Puspitasari (Indonesian Health Issue, 2025)
One type of cancer that most often affects women and is the cause of death worldwide is breast cancer. According to data from GLOBOCAN (2020) new cases of cancer in Indonesia reached 68,858 cases (16.6%) ofatotalof 396,914 newcasesin Indonesia. Lackof knowledge isoneof the factors for women to do early detection of breast cancer. Efforts to increase knowledge of adolescent girls are one of them through SADARI counseling. Breast self-examination (SADARI) aims to determine the presence or absence of lumps in a woman's breast. The purpose of this study was to determine the effect of providing educational video SADARI through video media on the level of knowledge of adolescent girls at SMAN 1 Pengasih Kulon Progo. This study used a pre-experiment method and used a one group pretest- postest approach. The population was 131 female students with 63young women in class XI used as samples selected using stratified random sampling technique. Data obtained through the distribution of questionnaires to respondents were then processed using the Wilcoxon test. This study has the results of the majority there is an increase in knowledge before being given intervention through SADARI video media with a majority of 29 respondents (46.03%) and after being given intervention as many as 37 respondents (58.73%). The results of the Wilcoxon test obtained a significant value of 0.000(p <0.05) which means Ho is rejected and Ha is accepted, meaning that there is an effect of providing health education using SADARI video media on the level of knowledge of adolescent girls at SMAN 1 Pengasih Kulon Progo. Suggestion: It is expected that the school is able to collaborate with the nearest health service to provide counselingon breastself-examination (SADARI) to all female students at SMA N 1 Pengasih Kulon Progo.